Expression of Desmoglein 3 (DSG 3) in different grades of oral squamous cell carcinoma and its correlation with lymph node metastasis (Bangladesh Journal of Medical Science, 2026)
Background/Objectives Oral squamous cell carcinoma (OSCC) remains a major global health challenge, with lymph node metastasis representing the most critical prognostic determinant. Desmogleins, transmembrane adhesion proteins, have emerged as potential biomarkers in cancer progression, yet their precise roles in OSCC metastasis remain incompletely characterized. This study is aimed to evaluate the expression patterns of desmoglein 3 (DSG3) in OSCC and to investigate its association with clinicopathological parameters using immunohistochemical analysis. Methods This retrospective study included 80 surgically treated OSCC patients who underwent tumor resection with neck dissection. Formalin-fixed, paraffin-embedded tissue specimens were subjected to immunohistochemical staining for DSG3. Expression patterns were categorized based on staining intensity and correlated with clinicopathological variables.. Statistical associations were assessed using appropriate tests, with p < 0.05 considered significant. Results The cohort comprised predominantly male patients (80.3%) with a mean age of 48 ± 8 years. Advanced disease was prevalent, with 77.3% presenting as Stage IV and 84.8% demonstrating nodal involvement (N+). Buccal mucosa (34.8%) and tongue (30.3%) were the most common primary sites. Histological grades were evenly distributed. DSG3 expression demonstrated highly significant associations with nodal involvement (p = 0.001) and advanced pathological stage (p = 0.001). Conclusions DSG3 expression is significantly associated with lymph node metastasis and advanced pathological stage in OSCC, demonstrating superior predictive capacity compared to conventional histological grade. These findings support the potential utility of DSG3 as a molecular biomarker for risk stratification of occult nodal disease and treatment planning in OSCC patients.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S259-S268